(untitled) (Agora for Physical Education and Sport, 2020)
This study aims to analyze body composition, the weekly physical-sports practice and nutritional habits in secondary school students. Sixty subjects (1.57 ± 0.07 m; 49.4 ± 10.5 kg), aged between 12 and 13 participated in this cross-sectional descriptive study. Body composition, weekly hours of physical-sports practice and nutritional intake were evaluated. It was differences between gender in the abdominal fold, thigh fold, biepicondyloid diameter, percentage fat, percentage muscle and fat weight (p <0.05). Participants agreed to the hours of physical-sports practice recommended by the experts. In both sexes, protein intake was higher than the recommended dietary intakes, coupled with an excess in the consumption of saturated fatty acids and a deficit in the intake of polyunsaturated fatty acids and fiber. Micronutrient intakes conform to the guidance. Aversely, the consumption of fruit, vegetables and ultra-processed was out of the expert advice. High school students, regardless of gender, follow the guidelines of daily physical-sports practice, there being a mismatch in the recommendations of consumption of fruit, vegetables and ultra-processed foods. The female gender has a higher fat percentage than the male gender in these ages.